CFD Modelling of a Pump as Turbine (PAT) with Rounded Leading Edge Impellers for Micro Hydro Systems - Al-Khalid, Hj Othman; Hushairi, Zen; Mohd Azlan, Ismail (EDP Sciences, 2017)
A Pump as Turbine (PAT) is one of micro hydro system components that is used to substitute a commercially available turbine due to its wide availability and low acquisition cost. However, PAT have high hydraulic losses due to differences in pumpturbine operation and hydraulic design. The fluid flowing inside the PAT is subjected to hydraulic losses due to the longer flow passage and unmatched fluid flow within the wall boundaries. This paper presents the effect of rounding the impeller leading edges of the pump on turbine performance. A CFD model of a PAT was designed to simulate virtual performance for the analysis. The aim of this study is to observe the internal hydraulic performance resulting from the changes in the performance characteristics. Highest efficiency was recorded at 17.0 l/s, an increase of 0.18%. The simulation results reveal that there is an improvement in hydraulic performance at overflow operation. The velocity vector visualization shows that there is a reduction in wake and consequently less flow separation along impeller flow passages. However, adjusting the sensitive impeller inlet geometry will also alter the velocity inlet vector and consequently change the velocity triangles for the turbo machinery system.